Qualitative and quantitative meta-analysis of acupuncture effects on the motor function of Parkinson's disease patients - Lei, Suying; Fan, Jingqi; Liu, Xin; Xv, Xiaoyan; Zhang, Jiayan; Zhou, Zipu; Zhuang, Lixing (Frontiers in Neuroscience, 2023)
Objective: To explore the association between acupuncture sessions and its effects on the motor function of Parkinson's Disease (PD). Methods: Eight databases and two clinical trials registries were searched from inception to August 2022. Randomized controlled trials(RCTs) that compared acupuncture with sham acupuncture, or antiparkinsonian drugs, were included. After qualitative meta-analysis, a non-linear meta regression approach with restricted cubic spline was used to investigate the dose-response relationship between acupuncture sessions and their efficacy on the Unified Parkinson's Disease Rating Scale Part Ⅲ (UPDRS-Ⅲ) score. Subgroup meta-analysis was performed of the included studies according to the weekly acupuncture frequency. And finally, the included studies containing the determination of intermediate efficacy were compared . Results: Of the 268 citations screened, 16 studies (462 patients of PD) were included. The qualitative meta-analysis showed that the acupuncture group had better effect on UPDRS-Ⅲ scores than the control group. And the quantitative meta-analysis suggested that acupuncture dose was correlated with the reduction of UPDRS-Ⅲ score in PD patients with motor symptoms. In subgroup analysis, on the one hand, when the frequency of acupuncture was no more than 3 times a week, with the increase of acupuncture session, the changes of UPDRS-Ⅲ score decreased and then increased(P = 0.000). On the other hand, when acupuncture for more than 3 times a week and the dose of acupuncture treatment was less than 60 times, the changes of UPDRS-Ⅲ score increased with the increase of acupuncture dose, but the score stopped to decrease if the dose continued to increase(P = 0.020). The comparative analysis of two quantitative RCTs found that the score improvement was more significant at the higher weekly acupuncture frequency. Interpretation: This study found that when treating PD patients with motor symptoms, acupuncture treatment may need to reach a certain dose to obtain better therapeutic effect and excessive acupuncture stimulation may cause the body to develop a certain tolerance. However, the above results still need to be verified by more high-quality clinical studies. The protocol was registered on PROSPERO International Prospective Register of Systematic Reviews (CRD42022351428).